Domesticating And Foreignizing Cultural Terms In Religious Texts: A Case Study Of Al-Baqara Sūrah In The Noble Qur’An - Ali Ayyad, Ghada Rajeh (2022)
This study aims to investigate the translation of cultural terms in the Noble Qur’an from Arabic into English by using the domestication and foreignization strategies. Three English translations of the Qur’an are selected to be studied. The data of this study are collected from Al-Baqarah Surah and its selected translations. Three main objectives have been proposed in this study. Firstly, to identify the more frequent strategy used by the translators to translate cultural terms. Secondly, to determine how the translators domesticated and foreignized cultural terms. Finally, to know which strategy of domestication and foreignization conveyed the meaning more adequately. The significance of this study arises from the fact that such studies may be used as a reference and a source for translators who are dealing with Qur’anic texts.